Post-Pandemic Recovery of the Global Economy - E. N. Smirnov (Vestnik MGIMO-Universiteta, 2021)
As the coronavirus pandemic continues to spread, the degree of its negative im- pact on the development of economic systems throughout the world economy increases. At the same time, the issues of the future world order and the restoration of the global econ- omy are becoming more and more uncertain. The purpose of our study was to review the conceptual and practical approaches to substantiating the possibilities of postcrisis recov- ery of the global economy in the context of the continuing negative impact of the pandemic on international trade, capital flows and the development of the world financial system. The article reviews the materials of international economic organizations to assess the longterm economic consequences of the pandemic. The analysis shows that the main problem in as- sessing the possibilities for the recovery of the world economy is the existing heterogeneity in the degree of the pandemic's impact on individual sectors and economies of countries, as well as the differentiation and inconsistency of the applied economic policy instruments. In addition, it was found that the world retains a high potential for financial instability, and “vaccine nationalism” is getting worse. The main contradiction is the transboundary nature of the challenges to further economic development with a significant slowdown in global- ization pro-cesses. The author considers the current pandemic to be one of the new global problems of the world economy, since its recovery in the current conditions is of an indefi- nite spasmodic nature, and there are also risks of a permanent slowdown in economic mo- bility. The solution to the key problem of economic growth - increasing productivity - is pos- sible only with a clear understanding and planning of progress with inclusive vaccination, which is so far elusive. Although shortterm economic policy is a priority for governments, a wellcoordinated international agenda is needed at the global level to ensure the transition from income support to stimulating economic growth, as well as to overcome the existing structural imbalances and distortions in the system of economic relations between coun- tries.